GITR Promotes the Polarization of TFH-Like Cells in Helicobacter pylori-Positive Gastritis - Ming, Siqi; Yin, Huan; Li, Xingyu; Gong, Sitang; Zhang, Guoliang; Wu, Yongjian (Frontiers in Immunology, 2021)
Gastric CD4+T cells contribute to Helicobacter pylori (H. pylori)-induced gastritis by amplifying mucosal inflammation and exacerbating mucosal injuries. However, the pathogenic CD4+ T cell subset involved in gastritis and the potential regulators are still unclear. Here we identified an IL-21-producing gastric CD4+T cell subset, which exhibited tissue-resident CXCR5−BTLA−PD-1hi TFH-like phenotype in H. pylori-positive gastritis patients. Meanwhile, we identified glucocorticoid-induced tumor necrosis factor receptor (GITR) as an important regulator to facilitate IL-21 production by CD4+T cells and accelerate mucosal inflammation in gastritis patients with H. pylori infection. Moreover, GITR expression was increased in gastric CD4+T cells of gastritis patients compared to healthy controls, along with the upregulated expression of its ligand GITRL in mucosal macrophages (Mϕ) of gastritis patients. Further observations showed that the activation of GITR/GITRL signal promoted the IL-21 production of CD4+T cells via the STAT3 pathway. Besides this, IL-21 from CD4+T cells induced the proliferation of B cell and promoted the production of inflammatory cytokines IL-1β and IL-6 and chemokines MIP-3α and CCL-25 as well as matrix metalloproteinase (MMP)-3 and MMP-9 by human gastric epithelial cells, suggesting the facilitating effect of IL-21-producing CD4+T cells on mucosal inflammation and injuries. Taking these data together, we revealed that GITR/GITRL signal promoted the polarization of mucosal IL-21-producing CD4+T cells in H. pylori-positive gastritis, which may provide therapeutic strategies for the clinical treatment of H. pylori-induced gastritis.